Acts of administration of ecclesiastical goods - ŚWITO, LUCJAN (Prawo Kanoniczne, 2017)
The Code of Canon Law (Corpus Iuris Canonici, CIC), in its version enacted by Pope John Paul II, employs diverse terminology when refer- ring to acts of administration of goods. Can. 1277 of CIC refers to “acts of administration which are more important” and “acts of extraordinary administration”, while the provision of 1281 §1 and §2 of CIC points out the dierence between “acts of ordinary administration” and “acts which exceed the limit and manner of ordinary administration”. Although the terminology adopted in the Code of Canon Law clearly marks the dierence, it does not dene these terms and does not provide any list of these acts. Scholars do not provide much opinion in this matter either, leaving the issue for consideration by particular legislation and legal practice. However, the exact denition of dierences between the above-mentioned acts of admi- nistration is of great practical importance for the validity of acts related to the administration of ecclesiastical property. e article presented herein, based on an analysis of Can. 1277 and Can. 1281 §1, and §2 of CIC, indicates the existing dierences in terminology, and underlines the urgent need to develop a list of extraordinary acts of administration of ecclesiastical goods to ensure the stability of this kind of legal action, and draws attention to the criteria by which acts of extraordinary administration should be formulated.